Assessment of acquired mucociliary clearance defects using micro‐optical coherence tomography. Issue 9 (28th June 2017) - Tipirneni, Kiranya E.; Grayson, Jessica W.; Zhang, Shaoyan; Cho, Do‐Yeon; Skinner, Daniel F.; Lim, Dong‐Jin; Mackey, Calvin; Tearney, Guillermo J.; Rowe, Steven M.; Woodworth, Bradford A.
Abstract : Background: Dehydration of airway surface liquid (ASL) disrupts normal mucociliary clearance (MCC) in sinonasal epithelium, which may lead to chronic rhinosinusitis (CRS). Abnormal chloride (Cl − ) transport is one such mechanism that contributes to this disorder and can be acquired secondary to environmental perturbations, such as hypoxia at the tissue surface. The objective of this study was to assess the technological feasibility of the novel micro‐optical coherence tomography (μOCT) imaging technique for investigating acquired MCC defects in cultured human sinonasal epithelial (HSNE) cells. Methods: Primary HSNE cell cultures were subjected to a 1% oxygen environment for 12 hours to induce acquired cystic fibrosis transmembrane conductance regulator (CFTR) dysfunction. Ion transport characteristics were assessed with pharmacologic manipulation in Ussing chambers. ASL, periciliary fluid (PCL), and ciliary beat frequency (CBF) were evaluated using μOCT. Results: Amiloride‐sensitive transport (ΔISC ) was greater in cultures exposed to hypoxia (hypoxia: −13.2 ± 0.6 μA/cm 2 ; control: −6.5 ± 0.1 μA/cm 2 ; p < 0.01), whereas CFTR‐mediated anion transport was significantly diminished (hypoxia: 28.6 ± 0.3 μA/cm 2 ; control: 36.2 ± 1.6 μA/cm 2 ; p < 0.01), consistent with acquired CFTR dysfunction and sodium hyperabsorption. Hypoxia diminished all markers of airway surface function microanatomy as observed with μOCT, including ASL (hypoxia: 5.0 ± 0.4 μm; control: 9.0 ± 0.9 μm; p < 0.01) and PCL depth (hypoxia: 2.5 ± 0.1 μm; control: 4.8 ± 0.3 μm; p < 0.01), and CBF (hypoxia: 8.7 ± 0.3 Hz; control: 10.2 ± 0.3 Hz; p < 0.01). Conclusion: Hypoxia‐induced defects in epithelial anion transport in HSNE led to predictable effects on markers of MCC measured with novel μOCT imaging. This imaging method represents a technological leap forward and is feasible for assessing acquired defects impacting the airway surface.